Intellectual Capital on Innovation Performance: The Mediating Role of Inter-Organizational Learning in Frozen Shrimp SMEs - Budi Hasyim; Cheng-Wen Lee; Datu Razali Datu Eranza; Romi Ilham; Aswan Aswan; Sherlyna Nur’Aini (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the effect of intellectual capital on innovation performance of frozen shrimp SMEs in North Kalimantan, with inter-organizational learning as a mediator. Research Method: A quantitative survey was conducted on 278 SMEs. Data were collected using structured questionnaires and analyzed with PLS-SEM to test direct and mediating relationships among variables. Results and Discussion: Intellectual capital significantly improves both inter-organizational learning and innovation performance. Inter-organizational learning has the strongest effect on innovation, indicating that collaboration and knowledge exchange with external partners are critical. It also mediates the relationship between intellectual capital and innovation performance, showing that internal resources become more effective when supported by external learning. Implications: The findings suggest that SMEs should strengthen knowledge-based resources and expand collaborative networks to enhance innovation. Policymakers should support capacity building and partnerships. Future studies may include additional variables or sectors for broader insights.